Pet owners' perceptions about the use of euthanasia in Lima, Peru - Phillips, Cinthia (2023)
The objective of the study was to describe the criteria used by pet owners in Metropolitan Lima when they decide to resort to euthanasia. The study developed corresponded to an observational, descriptive, and cross-sectional study. It used surveys implemented in Google Forms format. The survey data were automatically stored in a Google Excel database and summarized using descriptive statistics. Of the 405 pet owners surveyed, the majority were female (75.1 %), between 26 and 50 years of age (55.1 %), and had a university education (78.8 %). Likewise, 99.8 % of participants had heard about euthanasia; 50.1 % had used this service for an animal they owned; 99.0 % considered that they decided to use this procedure for relevant and appropriate reasons. Ninety-six percent mentioned that they received advice from a veterinarian in order to make an informed decision; 50.7% stated that it is necessary to implement a unique environment for euthanasia; 96.1% thought that euthanasia was the best choice to alleviate the suffering of the pet and the family; and 78.3% mentioned that they were affected by the decision. Of the total number of respondents, 90.4% agreed with the practice of euthanasia in animals, and 95.3% indicated that the veterinarian should recommend euthanasia if considered necessary. From the results of the study, it is concluded that there is a need for the veterinarian in charge of euthanasia to handle open, respectful, and understandable communication skills, in addition to the need to receive training in psychological strategies to offer euthanasia services when required, as well as to handle in the best way the affliction caused by the decision taken by the owner, who should be assisted in those moments.